A coupled finite-volume CFD solver for two-dimensional elasto-hydrodynamic lubrication problems with particular application to rolling element bearings. (May 2017) - Hajishafiee, A.; Kadiric, A.; Ioannides, S.; Dini, D.
Abstract: This paper describes a new computational fluid dynamics methodology for modelling elastohydrodynamic contacts. A finite-volume technique is implemented in the 'OpenFOAM' package to solve the Navier-Stokes equations and resolve all gradients in a lubricated rolling-sliding contact. The method fully accounts for fluid-solid interactions and is stable over a wide range of contact conditions, including pressures representative of practical rolling bearing and gear applications. The elastic deformation of the solid, fluid cavitation and compressibility, as well as thermal effects are accounted for. Results are presented for rolling-sliding line contacts of an elastic cylinder on a rigid flat to validate the model predictions, illustrate its capabilities, and identify some example conditions under which the traditional Reynolds-based predictions deviate from the full CFD solution. Highlights: A new, CFD based numerical method for modelling EHD lubrication is presented. The model utilises finite volume technique for both fluid and solid domains to produce a two-way coupled FSI model. The model is implemented in open source package OpenFOAM and validated against published data. Stability over a wide-range of conditions including those found in practical bearing applications is illustrated. An example case where CFD predictions deviate from Reynolds based approaches is shown.